Active Pedicle Epithelial Flap Transposition Combined with Amniotic Membrane Transplantation for Treatment of Nonhealing Corneal Ulcers. (17th October 2016) - Zhang, Ting; Wang, Yuexin; Jia, Yanni; Liu, Dongle; Li, Suxia; Shi, Weiyun; Gao, Hua
Abstract : Introduction . The objective was to evaluate the efficacy of active pedicle epithelial flap transposition combined with amniotic membrane transplantation (AMT) in treating nonhealing corneal ulcers. Material and Methods . Eleven patients (11 eyes) with nonhealing corneal ulcer who underwent the combined surgery were included. Postoperatively, ulcer healing time was detected by corneal fluorescein staining. Visual acuity, intraocular pressure, surgical complications, and recurrence were recorded. Corneal status was inspected by the laser scanning confocal microscopy and anterior segment optical coherence tomography (AS-OCT). Results . The primary diseases were herpes simplex keratitis (8 eyes), corneal graft ulcer (2 eyes), and Stevens-Johnson syndrome (1 eye). All epithelial flaps were intact following surgery, without shedding or displacement. Mean ulcer healing time was10.8 ± 3.1 days, with a healing rate of 91%. Vision significantly improved from 1.70 to 0.82 log MAR (P = 0.0 0 1 ). A significant decrease in inflammatory cell infiltration and corneal stromal edema was revealed 2 months postoperatively by confocal microscopy and AS-OCT. Corneal ulcer recurred in 1 eye. None of the patients developed major complications. Conclusion . Active pedicle epithelial flap transposition combined with AMT is a simple and effective treatment for nonhealing corneal ulcers.